2018
DOI: 10.1177/0011000018759769
|View full text |Cite
|
Sign up to set email alerts
|

“They Were Going to Kill Me”: Resilience in Unaccompanied Immigrant Minors

Abstract: Unaccompanied and undocumented immigrant minors (UUIM) have become the focus of increased attention. Unfortunately, public discourse is often decontextualized, simplistic, and polarized. Empirical literature fails to capture the experiences of UUIM and identify strategies to promote their well-being. In this article we begin to address these gaps through qualitative inquiry. We analyzed written narratives of 292 Latino UUIM using a theoretical thematic analysis. Participants described motives for, and experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The desire for family reunification is explicitly identified as a motive for migration in the following quotations drawn from Becker Herbst et al's (2018) Orozco and Yansura (2014) reported that, in their survey of adult immigrants from the NTCA, between 12% and 16% of respondents named family reunification as the main cause for the migration of unaccompanied children (p. 15). The Guatemalan NGO staff members interviewed by Nichols et al (2017) affirm that it is not only children who wish to be reunited with parents, but also migrant parents who plan to send for their children once they are economically stable and the children are old enough to make the journey on their own (p. 1979).…”
Section: Evidence From Childrenmentioning
confidence: 99%
“…The desire for family reunification is explicitly identified as a motive for migration in the following quotations drawn from Becker Herbst et al's (2018) Orozco and Yansura (2014) reported that, in their survey of adult immigrants from the NTCA, between 12% and 16% of respondents named family reunification as the main cause for the migration of unaccompanied children (p. 15). The Guatemalan NGO staff members interviewed by Nichols et al (2017) affirm that it is not only children who wish to be reunited with parents, but also migrant parents who plan to send for their children once they are economically stable and the children are old enough to make the journey on their own (p. 1979).…”
Section: Evidence From Childrenmentioning
confidence: 99%
“…Between October 1, 2015, and August 31, 2016, the U.S. Customs and Border Patrol apprehended nearly 55,000 undocumented, unaccompanied immigrant minors at the border of the southwest region of the United States (U.S. Customs and Border Protection, 2016). UUIM cross the border into the United States to afford themselves and their families a better future (Aldarondo & Becker, 2011;Becker Herbst et al, 2018). UUIM have reported taking a perilous journeys characterized by extreme hunger and thirst, physical injuries, illness, risk of physical harm, and poor treatment from immigration officials (Becker Herbst et al, 2018).…”
Section: Undocumented Immigrantsmentioning
confidence: 99%
“…UUIM cross the border into the United States to afford themselves and their families a better future (Aldarondo & Becker, 2011;Becker Herbst et al, 2018). UUIM have reported taking a perilous journeys characterized by extreme hunger and thirst, physical injuries, illness, risk of physical harm, and poor treatment from immigration officials (Becker Herbst et al, 2018). Youth who enter the U.S. immigration system are held in custody by the subsidiary agencies of the U.S. Department of Homeland Security.…”
Section: Undocumented Immigrantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unaccompanied immigrant children as students face a myriad of problems when familial resources are unavailable (Herbst et al, 2018). This student population is at-risk and faces profound disadvantages when they begin school.…”
Section: Rationalementioning
confidence: 99%